Consumer Satisfaction Regarding Anthurium Ornamental Plants (A case study conducted in Nglurah Village, Tawangmangu District, Karanganya Regency) - Setiawan, Feri; Mahananto (Journal of Rural and Urban Community Studies, 2024)
Ornamental plants encompass a wide array of plant species cultivated for their aesthetic beauty, resulting in diverse variations. Anthurium, known for its varied leaf patterns, presents an advantage in facilitating the creation of new hybrids. This study aims to identify and examine the characteristics of Anthurium ornamental plant consumers and analyze their satisfaction levels in Dusun Nglurah, Tawangmangu District, Karanganyar Regency. Employing a qualitative research method, this study utilized accidental sampling for data collection, incorporating both primary and secondary data sources through questionnaires and interviews. Findings reveal that the highest percentage of consumer satisfaction with Anthurium ornamental plants falls within the 20-30 age group (31%), predominantly comprising high school graduates (69%) employed as shop assistants, private sector employees, civil servants, farmers, or banking professionals (40%). Furthermore, 73% of consumers visit ornamental plant centers, with 67% citing plant variety as their primary purchase motivation. The majority of consumers (72%) purchase fewer than three plants, preferring a maximum price range of 0-5 million Indonesian Rupiah (IDR) (85%). Anthurium is the preferred plant species among consumers (53%), typically displayed in pots (WS = 0.84). Attributes such as rarity, uniqueness, variety, and price of the plants also scored a WS value of 0.84. Overall consumer satisfaction with Anthurium ornamental plants at the Ornamental Plant Center falls within the "satisfied" category, with a CSI value of 83.80%.